PENGARUH LUMPUR SAWIT FERMENTASI DENGAN SUPLEMENTASI ASAM AMINO LISIN, METIONIN, TRIPTOPAN SELAMA PRODUKSI TERHADAP PERFORMANS DAN KUALITAS INTERNAL SERTA KADAR KOLESTEROL TELUR AYAM RAS - Yosi Fenita; Desia Kaharuddin (BPFP Faperta UNIB, 2011)
The aim of this study was to evaluate the effect of feeding fermented palm oil sluge and critical amino acid (CAA) ; methyonine, lysine, and tryptophan supplementation on diet to performance, egg internal quality and egg cholesterol level. The research design used was complety randomized design with 4 teatments with 80 layer; each treatment consists of P0 ; the control diet, without addition of critical amino acid. P1 ; the diet contains of 50% critical amino acid (P1:50% (Lys 404.5 mg/kg ; Met 250 g/kg ; Trp 90,5 gr), P2: suplementasi 75% (Lys 606,75 mg/kg; Met 375,75 mg/kg; Trp 137,75 mg/kg), P3: suplementasi 100% (Lys 809 mg/kg; Met 501 mg/kg; Trp 90.5mg/kg) on diet.. Variable 0bserved were feed comsumption, feed conversi, egg weight, egg production, yolk colour, yolk index, albumen index, shell thickness, air cell and egg cholesterol level that feeding 100% supplementation consisting of (Lys 809 mg/kg; Met 501 mg/kg; Trp 90.5 mg/kg) significantly (P<0.05). In conclutions, P3 (Lys 809 mg/kg; Met 501 mg/kg; Trp 90.5 mg/kg) teatment group was significant on yolk colour, yolk index, albumen index, air cell and cholesterol level.